DOI: 10.26686/wgtn.23137601
|View full text |Cite
|
Sign up to set email alerts
|

Using Palaeomagnetic Techniques to Uncover the History of an Archaeological Site in Napier, Hawkes Bay

Shefali Poojary

Abstract: <p><b>Fired archaeological features and artefacts may carry records of the geomagnetic field at the time they were last used. During the 2020 demolition of early-mid 20th-century residential properties in central Napier/Ahuriri, an archaeological site was exposed. Six features, including two well-preserved hāngī (NP1 and NP2), two shallow fire-scoops (NP4 and NP6), baked floor of pumice-lined hearth (NP5) and a reddened pumice hearthstone (NP3) were excavated from beneath buried surface covered wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The thermoremanent magnetization imparted to hāngī stones during the heating and cooling process is typically strong and stable. It is often carried by magnetic minerals (magnetite, titanomagnetite and/or possibly maghaemite) that are themselves formed or enhanced in the heating process [12,13]. Further chemical alteration to the magnetic minerals is unlikely, due to the preservation of the archaeological features and their relative youth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The thermoremanent magnetization imparted to hāngī stones during the heating and cooling process is typically strong and stable. It is often carried by magnetic minerals (magnetite, titanomagnetite and/or possibly maghaemite) that are themselves formed or enhanced in the heating process [12,13]. Further chemical alteration to the magnetic minerals is unlikely, due to the preservation of the archaeological features and their relative youth.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we calculate feature mean ChRM directions by averaging specimen data, rather than sample mean data. Poojary [12] has shown that the actual mean directions rarely differ significantly. However, the calculated confidence in the mean is inevitably poor if only a small number of sample means are averaged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations